2008
DOI: 10.1177/000313480807401030
|View full text |Cite
|
Sign up to set email alerts
|

100 Robotic-Assisted Laparoscopic Gastric Bypasses at a Community Hospital

Abstract: Laparoscopic Roux-en-Y gastric bypass (LGB) is one of the most popular surgeries for morbid obesity. Robotic use is also on the rise. Data concerning outcomes is limited, hence the need for more information. The first 100 robotic-assisted bypasses by one surgeon in one institution were studied. Data obtained from clinic notes and hospital records included all who underwent the procedure. There were 79 females and 21 males. Mean age and body mass index were 42 years and 48 kg/m2, respectively. Comorbidities inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For the robotic series, most authors have noted a significant and rapid learning curve. Deng and Lourie [15] described a mean operative time of 200 min for their first 30 cases versus 184 min for the second 30 ( P = 0.03). Likewise, Hubens et al [13] reported that the total operative time decreased from 231 to 136 min ( P < 0.05) after the first 35 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the robotic series, most authors have noted a significant and rapid learning curve. Deng and Lourie [15] described a mean operative time of 200 min for their first 30 cases versus 184 min for the second 30 ( P = 0.03). Likewise, Hubens et al [13] reported that the total operative time decreased from 231 to 136 min ( P < 0.05) after the first 35 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal leak rate for the robotic gastric bypass reported in the literature varies from 0 to 3% (Table 3) [3–15]. Earlier experiences by Moser and Horgan [3] demonstrated a 0% leak rate and 1% stricture rate, well below the reported rates for traditional laparoscopic gastric bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgery is being incorporated into general surgical practice. During the last decade, the advent of the da Vinci Surgical System (Intuitive Surgical, Sunnyvale, CA, USA) has enabled many complex procedures to be performed with minimally invasive techniques in bariatric surgery [ 3 ]. Roux en Y gastric bypass remains one of the most challenging procedures performed by bariatric and general surgeons [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…– Bariatric outcome (postoperative Body Mass Index): only few trials reported the reduced mean BMI after 3 months from the RYGB [ 7 , 8 , 18 , 24 , 27 , 28 ] and SG [ 20 ] (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%